STATUS GIZI DAN LAMA RAWAT INAP PASIEN COVID-19 DI RS RUMAH SEHAT TERPADU DOMPET DHUAFA - Bayu Saputra, (Forum Ilmiah Kesehatan (FORIKES), 2022)
Several factors worsening the prognosis of the new coronavirus SARS-CoV-2 have been identified, such as obesity or diabetes. However, although nutritional status may change during the Covid-19 social distancing period, little is known about the effect of nutritional status among patients hospitalized with Covid-19. This study aims to assess whether nutritional status is related to length of stay in patients with Covid-19 in the hospital. The study was conducted on 188 patients who were hospitalized for Covid-19, using a cross-sectional design. The research sample was selected using a purposive sampling technique. The independent variable in this study was the patient's nutritional status as measured using the Body Mass Index (BMI) and length of stay as the dependent variable. All data comes from the patient's electronic medical record. The statistical test results showed a p value = 0.084, so it can be said that there is no relationship between nutritional status and the length of stay of Covid-19 patients in the hospital. Nonetheless, it is important to pay attention to providing good nutritional care according to patient needs, especially in the case of older adults with chronic or acute comorbidities.